Analysis of Students' Critical Thinking Levels in Geography Education through the Outdoor Learning Approach at SMA Negeri 4 Padang - Ade Irma Suryani; Jamaris Jamna; Yurni Suasti (JPG (Jurnal Pendidikan Geografi), 2026)
This study aims to analyze students’ critical thinking skills through the application of the outdoor learning model in Geography subjects at the senior high school level. Critical thinking is an essential competence in 21st-century education and plays a crucial role in helping students understand geographical concepts through real-world experiences. This research employed a quasi-experimental design involving an experimental class and a control class. The experimental class was taught using the outdoor learning model, which emphasizes direct observation, exploration, and interaction with the surrounding environment, while the control class received conventional instruction commonly applied by teachers, such as lectures and question-and-answer activities. The population of this study consisted of 120 eleventh-grade students, from which a sample of 52 students was selected, including 26 students from class XI IPS 4 as the experimental group and 26 students from class XI IPS 2 as the control group. Data were collected using a critical thinking questionnaire developed based on critical thinking indicators and analyzed descriptively to compare students’ performance in both groups. The results revealed that students in the experimental class achieved an average score of 82.19%, which was categorized as good and highly critical, while students in the control class obtained an average score of 79.80%, categorized as fairly good and moderately critical. These findings indicate that the outdoor learning model has a positive impact on improving students’ critical thinking skills and learning outcomes in Geography by encouraging active participation, contextual learning, and meaningful engagement with geographical phenomena. Therefore, the outdoor learning model can be considered an effective alternative instructional approach for enhancing students’ higher-order thinking skills in Geography education.